Involvement in Malaysians' physical activities and e-sports during the COVID 19 Movement Control Order (MCO) 2020 (International Journal of Physiotherapy, 2022)
Background: During the pandemic COVID19 in 2020, Movement Control Order (MCO) was implemented worldwide, including in Malaysia. This MCO restricts the movement and activities of the public to limit the community involvement in physical activity such as sports, exercise, and recreational activities. Therefore, this study was conducted to identify the trend of involvement of Malaysian people in sports, exercise, and recreational activities while MCO.Methods: This pilot survey was conducted among 150 randomly selected respondents from the enumerators around Kuala Lumpur, Selangor, and Putrajaya. Malaysia Sports Culture Index questionnaire (2018), with high validity and reliability used to collect the data. The data were analyzed descriptively using Statistical Package for Social Science (SPSS) version 26.Results: The findings showed that exercise was carried out by 60.5%, followed by e-sports by 19.5%, physical sports by 11.7%, and active recreation by 8.3%. Aerobics, walking, yoga, Zumba, and jogging are the five most frequent exercise activities in the exercise category. For the sports category, people prefer badminton and table tennis. The choice of time to be active during MCO shows the most common time is in the evening, 43.7%. This is followed by the morning option 28.8%, night time, 25.0%, and afternoon time, only 2.5%. Social media 78.7% is the most dominant medium used by Malaysians in performing sports activities, exercise, active recreation, or e-sports. On the other hand, some respondents used video conferencing 13.5% and conventional media 32.4% as a medium for being active.Conclusion: In particular, involvement in active sports and recreational activities declined significantly during the MCO. However, the dominant percentage of exercise activity plays a vital role in reducing the health risks associated with physical inactivity.